KEWENANGAN KOMISI PENYIARAN INDONESIA TERHADAP PENGAWASAN JASA PENYIARAN BERBASIS INTERNET - I Dewa Gede Herman Yudiawan; Made Sugi Hartono; Ni Luh Wayan Yasmiati (Program Studi Ilmu Hukum, Jurusan Hukum dan Kewarganegaraan, Fakultas Hukum dan Ilmu Sosial, Universitas Pendidikan Ganesha, 2023)
Broadcasts broadcast via television broadcasts have developed rapidly by presenting internet-based broadcasts or broadcasts. Looking at what currently exists in Indonesia, one of them is Vidio.com. Indonesia itself strongly adheres to the norms of politeness in social life, where internet-based broadcasting often displays scenes or words that are not in accordance with the norms of politeness that Indonesia currently adheres to. Article 13 paragraph (2) of Law No. 32 of 2022 regulates broadcasting services in Indonesia consisting of radio broadcasting services and television broadcasting services. Here it can be seen that the KPI does not have the authority to carry out supervision regarding internet-based broadcasting services. The authority possessed by KPI is attribution authority which originates from the law in carrying out broadcasting supervision in Indonesia. provisions of Bill C-11 and Law no. 32 of 2002 both regulate Broadcasting, but there are differences between these two provisions, Indonesia is limited to Radio and Television Broadcasting Services, while Bill C-11 Broadcast which has been revised, supervision covers Radio Broadcasting Services, Television, Providers Telecommunications and Internet Services. The internet in this case in Bill C-11 includes online streaming services. The supervision carried out by the CRTC is actually similar to that carried out by the KPI.